Analisa Perbandingan Metode Certainly Faktor – Naive Bayes Terhadap Diagnose Penyakit Pneumonia - Zalukhu, Erniwati (ADA Journal of Information System Research, 2024)
The development of science and technology is increasing rapidly, along with the progress of the times. Technology is becoming increasingly sophisticated and plays an important role in every aspect of life. currently growing rapidly. One disease that often attacks humans is pneumonia. Pneumonia is one of the diseases handled by the Estomihi Hospital on Jl. Sisingamangaraja No. 235 Kec. Medan City, Medan City. Pneumonia is a disease caused by viral bacteria and infects the respiratory tract. Diagnosis of pneumonia by using the certainty factor and naive Bayes methods is part of the expert system method which has a different way of working, resulting in a different percentage of confidence in the information. Given these differences, it is necessary to have an analysis that compares these two expert system methods to find and determine the best decision in diagnosing pneumonia. The percentage of Combination CF Value is only 55% while the percentage of Bayes Value is 67.6%.